Advancing musculoskeletal diagnosis and therapy: a comprehensive review of trigger point theory and muscle pain patterns - Zhai, Tianjun; Jiang, Fengyan; Chen, Yeping; Wang, Jie; Feng, Wei (Frontiers in Medicine, 2024)
Musculoskeletal disorders, especially chronic muscle pain, have a significant impact on public health, affecting millions worldwide. This review examines recent advancements in the diagnosis and management of myofascial pain, with a focus on the refined application of trigger point theory. This theory now incorporates an intricate model that blends biomechanical and neurophysiological mechanisms, essential for understanding the initiation and persistence of pain, and necessitating targeted therapeutic interventions.Utilizing a methodical approach, this paper categorizes muscle pain into three types: Muscle Belly Pain, Origin-Insertion Pain, and Referred Pain, as delineated in the most recent edition of "Myofascial Pain and Dysfunction -The Trigger Point Manual." Such classification enhances diagnostic precision and therapeutic effectiveness by establishing a specific treatment protocol for each type of pain. The paper discusses the implications of various treatments, such as dry needling and manual therapy, which are informed by empirically derived trigger point charts. These charts are instrumental in pinpointing the exact locations of pain sources and customizing treatment plans.Moreover, this review critically assesses the evolving nature of trigger point charts and champions a holistic approach to pain management. It underscores the necessity of integrating biomechanics, kinesiology, and compensatory mechanisms to provide a comprehensive understanding that allows practitioners to address not only symptomatic pain but also the root causes of musculoskeletal disorders, thereby enhancing long-term patient care outcomes in clinical environments.